Role of Duoderm (Hydrocolloid) Dressings in Bed Sores (Medical Forum Monthly, 2020)
Objective: To study the role of Duoderm (hydrocolloid) dressings in bed sores studyStudy Design: Observational and Experimental StudyPlace and Duration of Study: This study was conducted at the Department of Surgery and Medicine, Sialkot Medical College, Sialkot from March 2019 to March, 2020.Materials and Methods: One hundred patients of bed sore were included in this study to study the role of duoderm (hydrocoIIioid) dressing in this study. Demographic data was recorded in designed proforma. The history and examination was conducted on all the patients. Laboratory investigations for hepatitis C and complete blood examination was also conducted. The informed written consent was priorly taken in every case. The permission of ethical committee was also considered in this study. The data was analyzed for results on SPSS version 10.Results: The incidence of bed sore was maximum at the age of 50-60 years and minimum at the age of 20-30 year. Response to Duoderm application was maximum in polio patients and minimum in diabetic and spinal injury patients.Conclusion: Patient Response to Duoderm was quickest in upper class and in middle and lower class was comparatively low.